Bioinspired multilayer membranes as potential adhesive patches for skin wound healing - Sousa, M. P. (2018)
Bioinspired and adhesive multilayer membranes are produced using the layer-by-layer (LbL) assembly of chitosan (CHT), alginate (ALG) and hyaluronic acid modified with dopamine (HA-DN). Freestanding multilayer membranes without DN are also produced as a control. The success of the synthesis of HA-DN was confirmed using UV-visible spectroscopy. Scanning electron microscopy images indicate that the surface of the DN-containing membranes is more porous than the control ones; they also present a higher average thickness value for the same number of CHT/ALG/CHT/HA(-DN) tetralayers (n = 100). Also, water uptake, mechanical strength and adhesion are enhanced with the introduction of DN moieties along the nano-layers. Besides, human dermal fibroblast viability, enhanced adhesion and proliferation were confirmed by immunofluorescence assays and by measuring both the metabolic activity and DNA content. Moreover, in vivo assays with such kinds of DN-containing multilayer membranes were performed; the application of these membranes in the treatment of dermal wounds induced in Wistar rats results in the highest decrease of inflammation of rat skin, compared with the control conditions. Overall, this investigation suggests that these mussel-inspired freestanding multilayer membranes may enhance either their mechanical performance or cellular adhesion and proliferation, leading to an improved wound healing process, being a promising material to restore the structural and functional properties of wounded skin.